Towards dynamic multiscale feedback during the injection moulding cycle of plastics - Massano, Anabela P.; Vargas, Patricio; Carreira, Pedro; Matias, Joao; Malfois, Marc; Novo, Paulo J.; Martinho, Pedro; Pontes, Antonio; Mitchell, Geoffrey R. (Frontiers in Materials, 2024)
Injection moulding is a very popular technology for shaping plastics. It has a history which stretches back to the 19 th century and as a consequence it has developed outside the framework of digitialisation. In order to fully implement the concepts of Industry 4.0 we need to update these legacy technologies so that they can fully benefit from the developments inherent in the "internet of things" and allow the process of injection moulding to take full advantage of digital optimization so that it can fit effectively in the digital factory. In this work we are exploring the quantitative use of x-ray scattering as a technology which can provide dynamic and multiscale feedback during the injection moulding cycle to be able to exploit digital twin technology as a means to optimize the operational parameters involved in injection moulding and to enable digital design of moulds in the fullest sense. This manuscript provides a way marker for future work so as to draw these possibilities to a wider audience.